2017
DOI: 10.1007/s10926-017-9743-9
|View full text |Cite
|
Sign up to set email alerts
|

Work Participation Among Employees with Common Mental Disorders: A Meta-synthesis

Abstract: Purpose The aim was to aggregate knowledge about the opportunities, challenges and need for support employees with common mental disorders experience in relation to work participation in order to develop recommendations for practice. Methods A meta-synthesis was conducted using a meta-aggregative approach to accurately and reliably present findings that could be used to meet our aim. Qualitative inductive content analysis was used to analyze and synthesize the findings. Results In all, 252 findings were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 91 publications
1
27
0
Order By: Relevance
“…Our findings support previous studies in which employees with back pain describe not feeling understood because their health problems were invisible [15,22]. Many studies have stressed the need for a supportive and inclusive work environment for employees staying at work despite their health problems [23][24][25]. Our study adds to previous knowledge by expanding on how social support and a flexible working environment for employees with health problems can be achieved [8,9].…”
Section: What Was Already Known -What Does This Study Add?supporting
confidence: 88%
“…Our findings support previous studies in which employees with back pain describe not feeling understood because their health problems were invisible [15,22]. Many studies have stressed the need for a supportive and inclusive work environment for employees staying at work despite their health problems [23][24][25]. Our study adds to previous knowledge by expanding on how social support and a flexible working environment for employees with health problems can be achieved [8,9].…”
Section: What Was Already Known -What Does This Study Add?supporting
confidence: 88%
“…The results in this study show that experiences previously identified among long-term sick-listed such as demanding work and personal life (Thisted et al, 2018), social disruption (Froud et al, 2014), and uncertainty in balancing illness and RTW considerations (Andersen et al, 2012;Froud et al, 2014;Grant et al, 2019), were also relevant across health concerns at an early stage of long-term sick leave. These experiences demonstrate the complex and multidimensional aspects of sick leave, which could mean that multiple stakeholders with different perspectives may be needed in early interventions to assist sicklisted individuals back to work.…”
Section: Practical Implicationsmentioning
confidence: 54%
“…The importance of psychosocial factors in the RTW process are also demonstrated in findings that stressful family situations and a demanding work life are common experiences among long-term sick-listed individuals (Sandmark and Renstig, 2010;Frederiksen et al, 2015;Brataas and Evensen, 2016;Corbière et al, 2016). Meta-syntheses of qualitative RTW research also point to the disruption of social life during sick leave, stressful work situations, and the importance of supportive workplace for RTW, as common experiences (Froud et al, 2014;Thisted et al, 2018;Grant et al, 2019). The theory of role strain states that different obligations for the various social roles (e.g., at work, family, leisure) may not be compatible (Goode, 1960).…”
Section: Introductionmentioning
confidence: 96%
“…As mentioned above, there is a lack of research regarding RTW intention in relation to CMDs. However, a number of studies have investigated the importance of personal factors, that is, attitude, to RTW after sick leave due to CMDs as well as the individual's own experience of the RTW process (Andersen et al, 2012;Nielsen et al, 2013;Thisted et al, 2018). Furthermore, expectation concerning work ability (Victor et al, 2017) and confidence regarding RTW (RTW self-efficacy; Lagerveld et al, 2017) have been investigated among individuals on sick leave for CMDs.…”
Section: Introductionmentioning
confidence: 99%